2022
DOI: 10.1007/s10964-022-01599-0
|View full text |Cite
|
Sign up to set email alerts
|

How Do Adolescents Manage Information in the Relationship with Their Parents? A Latent Class Analysis of Disclosure, Keeping Secrets, and Lying

Abstract: The use of disclosure and concealment strategies by adolescents in the relationship with their parents may have important implications for their adjustment. Few studies of adolescents’ information management have taken a person-centered approach, yet it is a useful way to understand variations in how they regulate information shared with their parents. This study explored adolescents’ information management constellations with their mothers and fathers, and how these patterns differ in terms of perceived need-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 109 publications
(169 reference statements)
1
5
0
Order By: Relevance
“…As children develop into teenagers, these primary agents are partly ‘replaced’ by other identity models—such as friends or peers—that act as identity agents and self-recognition mediators (Balleys, 2015). In this, we echo the insights of other studies that examine parent-child negotiations during the onset of adolescence, when children begin to question parental self-patterns (Baudat et al, 2022). In other words, that moment when the child becomes reflexive and even critical of the way their parents’ name and assign meaning to the world.…”
Section: Primary and Secondary Socialization Processes And Screens Usessupporting
confidence: 76%
“…As children develop into teenagers, these primary agents are partly ‘replaced’ by other identity models—such as friends or peers—that act as identity agents and self-recognition mediators (Balleys, 2015). In this, we echo the insights of other studies that examine parent-child negotiations during the onset of adolescence, when children begin to question parental self-patterns (Baudat et al, 2022). In other words, that moment when the child becomes reflexive and even critical of the way their parents’ name and assign meaning to the world.…”
Section: Primary and Secondary Socialization Processes And Screens Usessupporting
confidence: 76%
“…In the present study it was identified that subjects with low scores on the Frankness scale are at risk for problematic alcohol, which is similar to what has been found in other studies [ 26 , 27 , 28 ]. Baudat et al, researched how teenagers manage information in their relationship with their parents and identified three types of information management strategies, namely Reserved, Communicators, and Deceptive [ 66 ]. They found that those in the Deceptive class were more likely to have problem drinking.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study examined multiple parenting behaviors specifically regarding media parenting (e.g., device access, communication and monitoring of online activities; Cox et al, 2021 ). A set of studies focused specifically on communication about substance use, incorporating parent-based and family communication styles ( Choi et al, 2017 ), topics and frequency of parent-teen communication about substance use ( Abar et al, 2011 ; Koning et al, 2012 ), and adolescent disclosure, secrecy, and lying ( Baudat et al, 2022 ). Across nearly all the disparate family based latent profiles, higher risk profiles emerged from combinations of known risk factors that were linked to substance use in expected directions.…”
Section: Methodological-conceptual Advancesmentioning
confidence: 99%